The Difficulties of Writing Descriptive Text for Junior High Schoolers - Vidya Mandarani; Fika Megawati; Adyansah Noer Pramoedya (Fakultas Ilmu Budaya, Universitas Brawijaya, 2022)
During the current pandemic, some schools have to implement hybrid learning, where some students come to school, and some have to go online. After the teacher gave the learning materials, some students who took online classes still did not understand it was different from students who took offline classes. The research used the qualitative method. The data was collected from 33 students in the 7b class and ten selected students based on their descriptive English writing text. It is revealed that the students have achieved reasonable control in writing descriptive text. However, in terms of writing, some students make spelling mistakes, and the use of tenses still needs more understanding. The result showed that the difficulties of descriptive writing are spelling, tenses, punctuation, sentence pattern, pronoun, conjunction, and preposition. They must consider schematic structures and use the appropriate language. Thus, their text will be well-organized and understandable.